Inflation dynamics in India: A structural view - Ramgopal Kundurthi; Siva Reddy Kalluru (PSL Quarterly Review)
The recent unprecedented global inflation has focussed attention on the supply side inflation dynamics. The Indian inflation episodes, however, have been largely associated with supply shortages and, on average, remained elevated through the last four decades, with different policy phases generating, at best, mixed results. This paper explores the Indian inflation dynamics through a structural paradigm, analysing factors such as sectoral growth imbalances and administered prices. The structural factors are observed to explain a significant part of the inflation, thus suggesting the need for government action on logistics management in the short term and structural reforms in the long run.